Friend or Foe or Family? A Tale of Formal and Informal Plants in India - Ghani, Ejaz; O'Connell, Stephen D.; Sharma, Gunjan (World Bank, Washington, DC, 2013)
This paper examines the interaction between formal (organized) and informal (unorganized) plants in the manufacturing sector in India. How has the size and productivity of the plants in the organized sector affected the plants in the unorganized sector? How have informal plants affected formal plants? Are the magnitudes of the effects symmetric in either direction? The evidence shows that there are positive horizontal and vertical spillovers in each direction. Informal firms are an important supplier of inputs to formal firms. Employment and output in the organized sector is greater in those states in India that have a greater presence of unorganized suppliers of inputs. Conversely, unorganized employment and output are greater in states that have a greater presence of organized buyers of inputs. But there are two important asymmetries in the relationship between the organized and unorganized sectors. First, the unorganized sector is much more dependent on and responsive to organized sector presence than vice versa. Second, unorganized sector productivity is dependent on and responsive to organized sector productivity and presence but the reverse is not true.